Commercially Available WO3 Nanopowders for Photoelectrochemical Water Splitting: Photocurrent versus Oxygen Evolution. Issue 9 (6th July 2016) - Reinhard, Sandra; Rechberger, Felix; Niederberger, Markus
Abstract: WO3 photoanodes with remarkable photocurrent densities are presented. These photoanodes were prepared from three different commercially available WO3 nanopowders. Doctor blading of the nanopowders followed by a short annealing in air led to nanostructured films. The best photoanode showed a photocurrent density of 3.5 mA cm −2 at 1.23 V vs. RHE in 1 m CH3 SO3 H under AM 1.5 G illumination (100 mW cm −2 ), surpassing values reported so far for bare WO3 photoanodes. The study also showed that the photocurrent was strongly dependent on the electrolyte, indicating oxidation of the electrolyte rather than of water. Oxygen evolution measurements performed in different electrolytes revealed that the amounts of oxygen were highly dependent on the electrolyte. By comparing the photocurrent values in the different electrolytes with the amount of evolving oxygen, it was found that the electrolyte producing the highest photocurrent was the electrolyte with the lowest oxygen evolution. Stability measurements showed that the more oxygen is produced, the less stable is the photoanode. These results clearly underline the difficulty to correlate the photocurrent values with oxygen evolution, drawing the attention to one of the major limitations of photoelectrochemical water splitting. Abstract : Photocurrent vs. oxygen evolution : Photoanodes with remarkable photocurrent densities up to 3.5 mA cm −2 at 1.23 V were produced from different commercial WO3 nanopowders (see figure). The strong dependency of the photocurrent and of the oxygen evolution on the electrolyte indicated oxidation of the electrolyte rather than of water. These results clearly underline the difficulty in balancing the photocurrent values with oxygen evolution.